PREVALENSI KEBUTAAN AKIBAT KATARAK DI RSUD DR. ZAINOEL ABIDIN BANDA ACEH - Eva Mardalena; Fauziah Hayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
The level of blindness caused by cataracts is the highest in Southeast Asia, which is 1.5% while in the WHO record, the level of blindness in Indonesia is ranked third in the world of 1.47%. The high rate of cataracts in Indonesia is influenced by geographical location in the equator so that based on the study assess the risk of 15 years earlier exposed to cataracts than residents in Europe. The purpose of this study was to determine the prevalence of blindness due to cataracts based on age, gender, visus and blind eye position. This research use descriptive method with cross sectional approach. The data source used is secondary data that is documentation data from medical record. Based on data analysis conducted, the results obtained that cataract patients who experienced blindness as much as 191 people, with blind men of 116 people. In the age group, obtained the most results at age 65 years that is equal to 89 people. Based on the location of the eye, the left eye (OS) more blindness than the eyes (ODS), and the most visus obtained blindness is 1/60 as many as 74 people. From this study obtained the conclusion that the prevalence of blindness due to cataracts in hospitals dr. ZainoelAbidin Banda Aceh amounted to 30.66%.Keywords: Blind, Cataract, Visus